2021
DOI: 10.51329/mehdioptometry119
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of phacoemulsification on the corneal endothelium in diabetic versus non-diabetic patients: a prospective non-randomized controlled interventional study

Abstract: Background: Cataract surgery in patients with diabetes is indicated either to improve visual acuity or to allow assessment and treatment of fundus changes. We aimed to document the effects of phacoemulsification on the corneal endothelium in patients with or without diabetes. Methods: This comparative, prospective, non-randomized controlled interventional study was conducted in patients with visually significant immature senile cataracts in the ophthalmology department at Sohag University Hospital betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Our comprehensive search for similar studies revealed 37 studies ( Table 1 ) [ 8 , 10 45 ]. Given the long study period (27 years), the cohorts differed in terms of phacoemulsification machines and parameters: for example, while longitudinal mode was used in the older studies and still predominated in the more recent studies, torsional and transversal modes have become increasingly favored ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our comprehensive search for similar studies revealed 37 studies ( Table 1 ) [ 8 , 10 45 ]. Given the long study period (27 years), the cohorts differed in terms of phacoemulsification machines and parameters: for example, while longitudinal mode was used in the older studies and still predominated in the more recent studies, torsional and transversal modes have become increasingly favored ( S1 Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying preoperative or surgical risk factors for endothelial-cell loss (ECL) after cataract surgery could improve outcomes: it could help determine which patients will require additional care or alternative treatment strategies and/or promote the development of new endothelial cell-sparing technical approaches. Our comprehensive analysis of the literature published since 1995 revealed a large field composed of 37 studies that have searched for such risk factors ( Table 1 ) [ 8 , 10 45 ]. However, all have significant limitations.…”
Section: Introductionmentioning
confidence: 99%
“…All participants underwent a full ophthalmic assessment, including an assessment of the best-corrected distance visual acuity using a Snellen chart (Topcon ACP-8R automatic chart projector, Topcon Corporation, Tokyo, Japan), a detailed anterior-segment slit-lamp examination [ 15 ] (Photo-Slit Lamp BX 900; Haag-Streit, Koeniz, Switzerland), and funduscopy with a +90-D lens (Volk Optical Inc., Mentor, OH, USA). Imaging examination of patients with T1DM included fundus photography, fundus fluorescein angiography (Topcon TRC 50IX fundus camera, Topcon, Tokyo, Japan), and macular assessment using a DRI Triton swept-source optical coherence tomography device (Topcon Corp., Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%